2012
DOI: 10.4314/mejs.v4i2.80114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bio-inoculants Applied to M<sub>5</sub> Mulberry Under Rain-fed Condition on Growth and Cocoon Traits Performance of Silkworm, <em>Bombyxmori</em> L.

Abstract: Nutrition plays a pivotal role in sericulture. It improves the growth, development, health, feed consumption and conversion of silkworm thereby improving the commercial traits. Silkworm, Bombyx Mori L., is a monophagous insect that drives almost all required nutrients for its growth and development from mulberry leaf. Application of the required nutrient in the required amount to mulberry plant is, therefore, very essential for the successful silkworm growth and cocoon production. The present investigation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The application Bio-fertilizer resulted in better values for silk gland length, pupation ratio, cocoon percentage and larval weight (ElKahyat 2013. These results are in agreement with those obtained by Rao et al, (2008), Mary and Saravanan (2010) and Waktole and Bhaskar (2012) who reported that nutrition plays a pivotal role in sericulture. It improves the growth, development, health, feed consumption and conversion of silkworm thereby improving the commercial traits.…”
Section: Sensilla Squamiformiasupporting
confidence: 93%
“…The application Bio-fertilizer resulted in better values for silk gland length, pupation ratio, cocoon percentage and larval weight (ElKahyat 2013. These results are in agreement with those obtained by Rao et al, (2008), Mary and Saravanan (2010) and Waktole and Bhaskar (2012) who reported that nutrition plays a pivotal role in sericulture. It improves the growth, development, health, feed consumption and conversion of silkworm thereby improving the commercial traits.…”
Section: Sensilla Squamiformiasupporting
confidence: 93%
“…Silkworm is a monophagous insect that drives almost all required nutrients for its growth and from mulberry leaf. Applicationof the required nutrient in a balanced amount to mulberry plant is, therefore, very essential for the successful silkworm growth and cocoon production Mary and Saravanan (2010) and Waktole and Bhaskar (2012).…”
Section: Resultsmentioning
confidence: 99%
“…Waktole and Bhaskar, 2012 [60] Effect of organic manures specially poultry manure in combination with Azotobactor bio fertilizers Indicated 50 percent reduction of inorganic nitrogen and 60% reduction of phosphorus application do not adversely affect plant growth, foliar constituents of mulberry when supplemented with the above bio-organic sources of amendments.…”
Section: Rao Et Al 2008mentioning
confidence: 99%